A comparison of video review and feedback device measurement of chest compressions quality during pediatric cardiopulmonary resuscitation. (August 2015) - Hsieh, Ting-Chang; Wolfe, Heather; Sutton, Robert; Myers, Sage; Nadkarni, Vinay; Donoghue, Aaron
Abstract: Aim: To describe chest compression (CC) rate, depth, and leaning during pediatric cardiopulmonary resuscitation (CPR) as measured by two simultaneous methods, and to assess the accuracy and reliability of video review in measuring CC quality. Methods: Resuscitations in a pediatric emergency department are videorecorded for quality improvement. Patients aged 8–18 years receiving CPR under videorecording were eligible for inclusion. CPR was recorded by a pressure/accelerometer feedback device and tabulated in 30-s epochs of uninterrupted CC. Investigators reviewed videorecorded CPR and measured rate, depth, and release by observation. Raters categorized epochs as 'meeting criteria' if 80% of CCs in an epoch were done with appropriate depth (>45 mm) and/or release (<2.5 kg leaning). Comparison between device measurement and video was made by Spearman's ρ for rate and by κ statistic for depth and release. Interrater reliability for depth and release was measured by κ statistic. Results: Five patients underwent videorecorded CPR using the feedback device. 97 30-s epochs of CCs were analyzed. CCs met criteria for rate in 74/97 (76%) of epochs; depth in 38/97 (39%); release in 82/97 (84%). Agreement between video and feedback device for rate was good ( ρ = 0.77); agreement was poor for depth and release ( κ 0.04–0.41). Interrater reliability for depth and release measured by video was poor ( κ 0.04–0.49). Conclusion: Video review measured CC rate accurately; depth and release were not reliably or accurately assessed by video. Future research should focus on the optimal combination of methods for measuring CPR quality.